Obligate parasitic fungi on the Tiligul Estuary coast (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
35 species of the order Erysiphales, 16 species of the order Peronosporales and 36 species of the order Pucciniales are recorded for the investigated territory. One species of the order Albuginales were presented on the Tiligul Estuary coast. 73 identified species are noted in the territory of two the same names regional landscape parks «Tiligulsky» (Mykolaiv and Odessa oblast). Some species of powdery mildew and rust fungi were found on the plants listed in the Red Data Book of Ukraine (2009), the European Red List and the List of CITES.
Keywords: Albuginales, Erysiphales, Peronosporales, Pucciniales, «Tiligulsky» regional landscape park, Ukraine.